2014
DOI: 10.1097/paf.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Fluid in the Airway of Nontraumatic Death on Postmortem Computed Tomography

Abstract: To evaluate radiographic features of endotracheal/endobronchial fluid in the airway (FA) observed on postmortem computed tomography (PMCT). We studied 164 subjects who died at our hospital between April 2009 and September 2012. Fluid in the airway was considered positive when fluid was identified in the lumen of 1 of the 2 main bronchi in continuity with a segmental bronchus. Pleural effusion and atelectasis/consolidation of the lung lower lobes were also evaluated. Fluid in the airway was observed in 60 (71%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…5A , arrowhead). In our previous study, fluid within the airway was frequently observed on postmortem CT in subjects with pleural effusion or atelectasis/pulmonary consolidation, and the volume of airway fluid increased over time postmortem ( 17 ).…”
Section: Increased Lung Density and Fluid Within Airwaysmentioning
confidence: 97%
See 1 more Smart Citation
“…5A , arrowhead). In our previous study, fluid within the airway was frequently observed on postmortem CT in subjects with pleural effusion or atelectasis/pulmonary consolidation, and the volume of airway fluid increased over time postmortem ( 17 ).…”
Section: Increased Lung Density and Fluid Within Airwaysmentioning
confidence: 97%
“…However, postmortem changes sometimes mimic pathologic lesions and vice versa. Although several studies have examined postmortem CT findings in individual organs ( 12 13 14 15 16 17 18 ), few have evaluated postmortem changes on whole-body postmortem CTs ( 19 20 ). In this pictorial essay, we present a case series of atraumatic in-hospital deaths, characterize the postmortem imaging features on postmortem CT, and discuss the pitfalls of postmortem CT examination and the differential diagnosis of postmortem CT findings.…”
Section: Introductionmentioning
confidence: 99%
“…Ishida et al demonstrated that in nontraumatic death cases, the appearance of fluid contents in the airways in PMCT correlated with the time after death [29]. Hyodoh et al showed a decreased aerated lung volume due to fluid accumulations over time after death [30].…”
Section: Limitationsmentioning
confidence: 98%
“…As guidelines for the diagnosis of postmortem images are now being established worldwide, it is important to understand the normal changes on postmortem CT. The postmortem CT features of several organs have already been described [7][11]. To our knowledge, however, there are no reports describing the postmortem changes in CT attenuation of striated muscle.…”
Section: Introductionmentioning
confidence: 97%